The importance of Iran’s nuclear deal for Biden’s diplomacy in Middle East (Халықаралық қатынастар және халықаралық құқық сериясы, 2021)
Multilateral agreements between countries around the world on challenging issues often pave the way for the parties to play a role in the developments following such agreements. The Joint Comprehensive Plan of Action (JCPOA) was such a tool for Iran to become an effective player in international bargaining at a time when Iran was trying to isolate itself by trying to build nuclear weapons. The deal that in 2018 US decided to withdraw from it. The American interests in the Middle East, on the one hand represent a single package that is affected by each other, and on the other hand it is the nature of the region’s crises and problems that is seen as an interconnected chain. The “Iran Nuclear Case” is important for future diplomacy of Biden in the Middle East.This paper describes the importance of deals for Middle East diplomacy of the US and which challenges in the way of the new President. The research is essentially important for the newly elected US President Biden’s foreign policy towards further relations with Iran that is widely estimated by experts for its positively changes in regional balance context. The scientific and practical essence of the paper is seemed to be as an expertise analyze towards enhancing the realistic approach for further isolating Iran in a time when the competition for strategic influence is being increased day by day. The methods used in paper is widely described in framework of as an analytical tool for the Middle East expert in terms of comparative, historical as well as descriptive analysis. The results of analysis might be useful for policy decision-makers as well as for academia that is to say the research conclusion is the Biden’s foreign policy in the Middle East would change its direction in comparison with Trump’s policy in the region. The article intends to have a small contribution in the social science in the context of today’s vague and biased approach in conceptualization of Middle Eastern impact to world affairs. As a final practical essence of the research is dedicated for US sanction policy for Iran’s place in the region by and large.Key words: Iran, USA, Biden, Diplomacy, Nuclear Deal.